ASPECTS REGARDING THE TECHNICAL EXPERTISE OF THE ROTATIONAL MECHANISM OF COAL MINING MACHINE - Part I - Marius Liviu CÎRŢÎNĂ; Constanța RĂDULESCU; Alin STĂNCIOIU (Fiabilitate şi Durabilitate)
In this paper we presents technical conditions for the rotational mechanism of the coal mining machine after we made technical expertise. The rehabilitation at the rotational mechanism will be subjected, it will be done by performing the intervention works who will restore both the structural part and the functional part in the normal operating parameters. The paper presents the defects found in the rotational mechanism as well as the proposed solutions for its repairs